2009
DOI: 10.1007/s11033-009-9927-2
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the bovine ADRB3 gene

Abstract: The β(3)-adrenergic receptor (ADRB3) is predominantly expressed in white and brown adipose tissue and mediates the lipolytic and thermogenic effects of high catecholamine concentrations. Variation in the ADRB3 gene (ADRB3) has been associated with obesity and the earlier onset of non-insulin-dependent diabetes mellitus in some ethnic groups, as well as some production traits of sheep, but to date variation of bovine ADRB3 has not been reported. In this study, variation in the promoter region of bovine ADRB3 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…However, in the liver, ADRB3 transcripts were found to be differentially expressed in the 10 % compared to the 0 and 20 % Spirulina groups. Given that the ADRB3 gene encodes proteins regulating mammalian energy storage and expenditure by mediating effects from the sympathetic nervous system (Hu et al 2010;Wu et al 2012), our observations suggest an intricate genetics-nutrition interaction underpinning transcription at the molecular level that can be dietarily manipulated to achieve healthy FA composition outcomes. In addition, we demonstrated that BTG2 transcription levels were significantly up-regulated in the liver of prime lambs supplemented with 20 % dietary Spirulina.…”
Section: Discussionmentioning
confidence: 95%
“…However, in the liver, ADRB3 transcripts were found to be differentially expressed in the 10 % compared to the 0 and 20 % Spirulina groups. Given that the ADRB3 gene encodes proteins regulating mammalian energy storage and expenditure by mediating effects from the sympathetic nervous system (Hu et al 2010;Wu et al 2012), our observations suggest an intricate genetics-nutrition interaction underpinning transcription at the molecular level that can be dietarily manipulated to achieve healthy FA composition outcomes. In addition, we demonstrated that BTG2 transcription levels were significantly up-regulated in the liver of prime lambs supplemented with 20 % dietary Spirulina.…”
Section: Discussionmentioning
confidence: 95%
“…Prior to sequencing, one of the unique bands representing each allele was cut out of the polyacrylamide gel (PAGE) and purifi ed by the method as described by Hu et al (2010). This was then used as the DNA template for reamplifi cation and sequencing.…”
Section: Dna Sequencing and Analysismentioning
confidence: 99%
“…The four patterns of these bands were uniform for all samples in this study. For the purposes of sequencing analysis, each band was cut from PAGE and then purified using TE wash buffer method (Hu et al, 2010). The results of purifications was used as a sample for reamplification process and sent to sequencing platform (Macrogen Inc., Korea).…”
Section: Identification Of Mstn Cdel960g By Using Pcr-sscp Methodsmentioning
confidence: 99%
“…Prior to sequencing, each band was cut out from PAGE and purified (Hu et al, 2010). This was then used as the DNA template for reamplification then sent to sequencing platform (Macrogen Inc., Korea).…”
Section: Sequencing and Sequence Analysismentioning
confidence: 99%